If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 7(x + 1) = 12 + 10x Reorder the terms: 5 + 7(1 + x) = 12 + 10x 5 + (1 * 7 + x * 7) = 12 + 10x 5 + (7 + 7x) = 12 + 10x Combine like terms: 5 + 7 = 12 12 + 7x = 12 + 10x Add '-12' to each side of the equation. 12 + -12 + 7x = 12 + -12 + 10x Combine like terms: 12 + -12 = 0 0 + 7x = 12 + -12 + 10x 7x = 12 + -12 + 10x Combine like terms: 12 + -12 = 0 7x = 0 + 10x 7x = 10x Solving 7x = 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 7x + -10x = 10x + -10x Combine like terms: 7x + -10x = -3x -3x = 10x + -10x Combine like terms: 10x + -10x = 0 -3x = 0 Divide each side by '-3'. x = 0 Simplifying x = 0
| x+3/4=17/18 | | 2(x+2)=1x-5 | | -10-9y=-13 | | 4/6x-2/6 | | 8/9*4/5 | | 7x-12x=-45+15 | | 4(y-3)-2y=5(3y+1) | | x-1=2(3x+7) | | 21-9x=4x+8 | | 3/6x-9/18 | | 64/1*7/8 | | 6x-5=4x-9 | | 3/4x-1+1/2x=7/16x+1/8 | | 1/2(x-6)=9 | | 5(y-4)=2(y+5)Y | | f(x)=x^3-x^2-11x+3 | | 5/6*2/3*2/7 | | x=(2.4e)/(0.68^1/5) | | 3/5*4/7*1/3 | | -9x^2+16x-14=0 | | 5(2x+3)=7(x+1) | | 0.11+0.09+720=1520 | | 17x+27x=180 | | 9/10*5/7*1/3 | | -16+2x=4x-4(4+3) | | 4x^2-15x+14=-6x+9 | | x=2.4e/(0.68)^1/5 | | -15+2x=45 | | -6x^2-23x-4=0 | | -3/4c=2 | | -5+3x=2x+0 | | x=2.4e/0.68 |